Non-dominant handgrip strength is associated with higher cardiorespiratory endurance and elevated NT-proBNP concentrations in ambulatory male adult outpatients with stable HFrEF - Triangto, Kevin; Radi, Basuni; Siswanto, Bambang B.; Tambunan, Tresia FU.; Heriansyah, Teuku; Harahap, Alida R.; Kekalih, Aria; Katsukawa, Hajime; Santoso, Anwar (Narra Sains Indonesia, 2024)
Understanding the significance of handgrip strength is essential for identifying frailty in heart failure patients. The aim of this study was to identify the association between handgrip strength and cardiorespiratory endurance while highlighting the importance of the musculoskeletal system in cardiac rehabilitation for patients with heart failure. An observational cross-sectional study was conducted at Harapan Kita Hospital, Jakarta, Indonesia, from April 2022 to April 2023, among patients with heart failure with reduced ejection fraction (HFrEF) attributed to cardiomyopathy or coronary artery disease. Patients were classified by a 6-minute walk test (6MWT) distance into <400 meters (low endurance) or ≥400 meters (high endurance). The short physical performance battery (SPPB), handgrip strength, ultrasonographic forearm muscle thickness, left ventricle ejection fraction, tricuspid annular plane systolic excursion, and N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels were measured. Results indicated significant differences in non-dominant handgrip strength, gait speed, and sit-to-stand SPPB scores between patients achieving a 6MWT distance of ≥400 meters and those below this threshold, with values of 31.11±6.88 kg vs 27.66±6.66 kg (p=0.049), 0.52±0.08 m/s vs 0.61±0.13 m/s (p=0.001), and 10.71±2.47 seconds vs 12.85±4.11 seconds (p=0.014), respectively. Stronger non-dominant handgrip strength (>30 kg) was associated with higher endurance (odds ratio (OR): 3.80; 95%CI: 1.35–10.67; p=0.010) and thicker forearm muscles (>1.9 cm) as measured by ultrasonography (AUC: 0.713; 95%CI: 0.585–0.840, p=0.001). In conclusion, a cut-off of ≤30 kg for non-dominant handgrip strength could effectively stratify the male patients into a lower endurance group (6MWT ≤400 meters), which is associated with elevated NT-proBNP levels and reduced forearm muscle thickness.